Obesity amongst Medical Students - A Cross-Sectional Comparative Study from Lahore, Pakistan, 2022 - Rozina Shahadat Khan, Sunair Siddique Khan, Romaisa Siddique (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Doctors wellbeing not only affects them but also it has strong impact on their surroundings as they are considered as role models in community. Aim: To assess the magnitude and any overtime change of obesity among the medical students. Methods: This study was conducted at Ameer Ud Din Medical College Lahore from February to April 2022. Informed verbal consent was taken from 159 students selected through simple Random sampling that agreed and were not having any health ailments like ascites or edema artificially increasing body weight and hormonal disorders. Analysis was done using SPSS v 23. Result: Based on BMI cut-off for Asians 21.38% medical students had BMI ≥25.0 kg/m2, 8.18% were underweight and all females. Significantly greater numbers of males were obese (BMI ≥25) as compared to females 25% (11 of 44) vs. 20% (23 of 115) and as well as in severe obese category (BMI ≥30) 11.36% (5 of 44) for male vs. 3.5% (4 of 115) females. Conclusion: Medical students have comparatively lesser prevalence than general public and this has improved over the passage of time and in comparison of similar population of the other province but has shown both increase in Pre-obesity prevalence and under nutrition trend in female medical students demanding to search the possible factors for this double burden Malnutrition among female medical students. Keywords: Obesity, Prevalence, MBBS Students.